EXPOSURE BERITA TERHADAP MINAT PARIWISATA LOMBOK PASCA GEMPA - Arianti, Gusmia (Universitas Prof. Dr. Moestopo (Beragama), 2019)
The focus of the research is looking at the influence of exposure to news that appears on television against the interest in visiting. The study was conducted with a survey method for 66 respondents, data collection was conducted in December 2018-February 2019, by using linear regression analysis. The exposure of the media to become an independent variable and interest in visits are dependent variables. The results showed that news exposure to television mass media about Lombok tourism after the earthquake in August 2018 then gave a significant positive effect on the interest of community visits to Lombok. Television is considered to play an important role in the dissemination of information. This is in accordance with the uses and effect theory, where the need for information will affect the behavior of recipients of information.